ANALISIS KESULITAN PENGUASAAN PERANGKAT PEMBELAJARAN BIOTEKNOLOGI PADA GURU BIOLOGI SMA SE-KABUPATEN LANGKAT - Firdaus Fahdi; Fauziyah Harahap; Herbert Sipahutar (Jurnal Pelita Pendidikan, 2016)
This study was conducted in SMA Se-Langkat which aims to determine the level of difficulty biologyteacher (1) SMA As Langkat; (2) that have been certified (3) that has not been certified in high schoolBiotechnology As Langkat; (4) which is taught in public schools; and (5) are taught in private schools. Thesesamples included 40 teachers of biology of the population 40 teachers from 19 high school biology As Langkat.The research instrument is a non tests that documentation, questionnaire, interview and observation sheet.The results showed the difficulty level biology teachers: (1) SMA As Langkat classified as moderate (58.61%); (2)that have been certified very low (18.42%); (3) that has not been certified is low (41.68%); (4) who teach inpublic schools classified as very low (28.64%); (5) who teach in private schools classified as very low (29.54%).Results of this study mengiplikasi importance of addressing the difficulties faced by teachers withcommunication between teachers of biology utilizing discussion forum subject teachers (MGMP) and the needto facilitate schools with facilities and infrastructure that support the learning success.Keywords: Analysis of the Difficulties Teachers, Learning Tools, Biotechnology